2022
DOI: 10.1136/jech-2021-218509
|View full text |Cite
|
Sign up to set email alerts
|

Residential mobility and potentially avoidable hospitalisations in a population-based cohort of New Zealand children

Abstract: BackgroundResidential moves are common in early childhood and associations have been found between residential mobility and adverse child health and well-being outcomes. Although there are studies on potentially avoidable hospitalisations (PAH) in children, few have examined PAH in relation to residential mobility. Our aim, therefore, was to investigate residential mobility and PAH in a population-based cohort of New Zealand children.MethodsUsing a retrospective cohort design, we analysed data from the Integra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Using the same cohort, potentially avoidable hospitalizations were determined from hospital discharge data. Half of the children had moved by age 2, and again the authors found a linear association between higher residential mobility and the increased likelihood of avoidable hospitalization (109).…”
Section: Stability and Mobilitymentioning
confidence: 87%
“…Using the same cohort, potentially avoidable hospitalizations were determined from hospital discharge data. Half of the children had moved by age 2, and again the authors found a linear association between higher residential mobility and the increased likelihood of avoidable hospitalization (109).…”
Section: Stability and Mobilitymentioning
confidence: 87%